2021
DOI: 10.1111/joim.13419
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to two doses of BNT162b2 vaccination in people with HIV

Abstract: Background. People with HIV (PWH) are at increased risk of severe COVID-19. We aimed to determine humoral responses in PWH and controls who received two doses of BNT162b2. Methods.In 269 PWH and 538 age-matched controls, we measured IgG and neutralizing antibodies specific for the receptor-binding domain of SARS-CoV-2 at baseline, 3 weeks and 2 months after the first dose of BNT162b2. Results.IgG antibodies increased from baseline to 3 weeks and from 3 weeks to 2 months in both groups, but the concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 15 publications
4
53
3
Order By: Relevance
“…First reports showed that most PLWH responded to mRNA vaccination in terms of binding and neutralizing Ab (82). This was consistent with observations made in a simian animal model (83).…”
Section: People Living With Hiv (Plwh)supporting
confidence: 86%
“…First reports showed that most PLWH responded to mRNA vaccination in terms of binding and neutralizing Ab (82). This was consistent with observations made in a simian animal model (83).…”
Section: People Living With Hiv (Plwh)supporting
confidence: 86%
“…In PLWH, the questionnaire was completed 1039 (90.0%) times after the first vaccination and 1026 (90.4%) after the second vaccination. Overall, more than half (52.4%) of the participants reported any AE ( Our primary result analysis in participants receiving mRNA vaccines contrasts with most of the small cohort studies performed in PLWH where the authors found similar responses as in controls [16][17][18].…”
Section: Reactogenicitycontrasting
confidence: 56%
“…Small studies using the ChAdOx1-S vaccine in the UK and South Africa in relatively young PLWH with high CD4+ T-cell counts gave comparable responses to controls [14, 15]. As for BNT162b2, similar results were shown in a limited number of PLWH [16-18]. The identification of risk factors for a reduced response to SARS-CoV-2 vaccines in PLWH is important as it will help to improve vaccination strategies in PLWH.…”
Section: Introductionmentioning
confidence: 88%
“…A positive humoral response was defined as having both a minimum of 25% inhibition in the neutralizing assay and concurrent anti-RBD IgG >225 AU/ml ( 28 , 32 ).…”
Section: Methodsmentioning
confidence: 99%